Digital Marketing Dan Brand Image Terhadap Intensi Pembelian Produk Susu Murni - Santoso, Rudi; Fianto, Achmad Yanu Alif; Erstiawan, Martinus Sony (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
Research aim : This study aims to measure digital marketing and brand image that can affect the purchase intention of pure flavored implant products (Sura's). Design/Methode/Approach : This study uses a survey research model Research Finding : The results of the study show that digital marketing and brand image have a significant effect on purchase intention. Theoretical contribution/Originality : This research also proves that digital-based marketing activities through Marketpalce and social media are very effective during the pandemic. Practitionel/Policy implication : digital marketing and brand image play a role in increasing sales. to increase the sales intention of these products, the management must improve digital marketing. Research limitation : This research only focuses on two variables, namely digital marketing and brand image.